Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1177/2042018815616543
|View full text |Cite
|
Sign up to set email alerts
|

Levothyroxine treatment of mild subclinical hypothyroidism: a review of potential risks and benefits

Abstract: Subclinical hypothyroidism (SCH) is defined as elevated thyroid stimulating hormone (TSH) with normal levels of free triiodothyronine (FT3) and free thyroxine (FT4). SCH is further classified into a milder condition with TSH levels between 4.0 and 10.0 milli-international units (mIU)/l (mild-SCH) and a severe form with TSH >10.0 mIU/l (severe-SCH). SCH is a common problem (prevalence is greater in women than men), which increases further with increasing age and TSH levels. Even though the risk of progression t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
62
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(65 citation statements)
references
References 109 publications
0
62
0
3
Order By: Relevance
“…First, we chose to set a thyrotropin target of 0.40 to 4.60 mIU per liter with levothyroxine treatment, which is an approach that reflects recent guidelines, particularly for older persons. 7 However, some authorities have recommended a lower thyrotropin target (e.g., 0.40 to 2.50 mIU per liter). 29 We cannot exclude the possibility that this more aggressive treatment approach might be beneficial.…”
Section: Thyroid Hormone In Subclinical Hypothyroidismmentioning
confidence: 99%
See 1 more Smart Citation
“…First, we chose to set a thyrotropin target of 0.40 to 4.60 mIU per liter with levothyroxine treatment, which is an approach that reflects recent guidelines, particularly for older persons. 7 However, some authorities have recommended a lower thyrotropin target (e.g., 0.40 to 2.50 mIU per liter). 29 We cannot exclude the possibility that this more aggressive treatment approach might be beneficial.…”
Section: Thyroid Hormone In Subclinical Hypothyroidismmentioning
confidence: 99%
“…Antibody-positive patients are more likely than antibody-negative patients to have progressive hypothyroidism and therefore may be more likely to have a benefit from long-term levothyroxine treatment. 7 Finally, our trial was underpowered to detect any effect of levothyroxine on the incidence of cardiovascular events or mortality. Therefore, we cannot exclude the possibility that treatment with levothyroxine may provide cardiovascular protection or cause harm.…”
Section: Thyroid Hormone In Subclinical Hypothyroidismmentioning
confidence: 99%
“…SCH is characterized by an increase in TSH levels that can range from 4.0 to 10.0 mIU/l in milder SCH and TSH >10.0 mIU/l in severe SCH [15,16] . Notwithstanding, SCH patients may present positive anti-thyroid peroxidase (TPO) antibodies, as well as a TSH level of between >2.0 mIU/l and <10.0 mIU/l [17] .…”
Section: Subclinical Hypothyroidismmentioning
confidence: 99%
“…[6,7] In hypothyroidism, respiratory muscle weakness is present in both inspiratory and expiratory muscles both affects pulmonary functions accordingly. [7][8][9] Researchers reported that pulmonary functions may decrease in hypothyroid females and after thyroid hormone replacement these values may increase significantly, [10][11][12][13] but studies are limited to the expiratory respiratory functions only. Moreover, the effect of hormone deficiency on expiratory and inspiratory flow rates was not found place in literature.…”
Section: Introductionmentioning
confidence: 99%